Steamboat PROSPECTOR and three scows on the Yukon River, Yukon Territory, 1901. - University of Washington Libraries. Special Collections Division
Caption on image: "The Prospector turning with scows in Fifty Mile River" Fifty Mile River is the portion of the Yukon River between Lake Marsh and Lake LaBerge. PH Coll 246.43 [Meed journal: "Steamer "Prospector" in 50 Mile River just below White Horse, Yukon. The 3 scows or barges are lashed firmly to the bow of the boat and pushed ahead. A loose towline is never used in river operations, as bends in the channel are often very short and sharp, and all risks of damage to the stern-paddle wheeler must be avoided. The cargo on this trip was beef-cattle below and sheep on a raised platform above them."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number